Sensitive operation of enzyme-based biodevices by advanced signal processing - Mazurenko, Stanislav; Bidmanova, Sarka; Kotlanova, Marketa; Damborsky, Jiri; Prokop, Zbynek (PloS one, 2018)
Analytical devices that combine sensitive biological component with a physicochemical detector hold a great potential for various applications, e.g., environmental monitoring, food analysis or medical diagnostics. Continuous efforts to develop inexpensive sensitive biodevices for detecting target substances typically focus on the design of biorecognition elements and their physical implementation, while the methods for processing signals generated by such devices have received far less attention. Here, we present fundamental considerations related to signal processing in biosensor design and investigate how undemanding signal treatment facilitates calibration and operation of enzyme-based biodevices. Our signal treatment approach was thoroughly validated with two model systems: (i) a biodevice for detecting chemical warfare agents and environmental pollutants based on the activity of haloalkane dehalogenase, with the sensitive range for bis(2-chloroethyl) ether of 0.01-0.8 mM and (ii) a biodevice for detecting hazardous pesticides based on the activity of γ-hexachlorocyclohexane dehydrochlorinase with the sensitive range for γ-hexachlorocyclohexane of 0.01-0.3 mM. We demonstrate that the advanced signal processing based on curve fitting enables precise quantification of parameters important for sensitive operation of enzyme-based biodevices, including: (i) automated exclusion of signal regions with substantial noise, (ii) derivation of calibration curves with significantly reduced error, (iii) shortening of the detection time, and (iv) reliable extrapolation of the signal to the initial conditions. The presented simple signal curve fitting supports rational design of optimal system setup by explicit and flexible quantification of its properties and will find a broad use in the development of sensitive and robust biodevices.
Keywords: Chemical Warfare Agents; Hexanes; Enzymes; chemické bojové látky; chlorované uhlovodíky; látky znečišťující životní prostředí; biosenzitivní techniky; hexany; enzymy; Hydrolases; Hydrocarbons, Chlorinated; hydrolasy; kalibrace; Ether; počítačové zpracování signálu; Biosensing Techniques; ether; Lyases; senzitivita a specificita; Sensitivity and Specificity; Environmental Pollutants; Signal Processing, Computer-Assisted; lyasy; Calibration